Substrate-morphology driven tunable nanoscale artificial synapse - Iqbal, Shahid; Kumar, Mohit; Singh, Ranveer; Sial, Qadeer Akbar; Seo, Hyungtak (Journal of Asian Ceramic Societies, 2021)
Two-terminal memristive devices are considering as a potential candidate to mimic human brain functionality to enable artificial intelligence. Particularly, two-terminal nanoscale devices are regarded as a promising solution for implementing bio-synapses due to their small dimensions, extremely compact, and low power to operate neuromorphic functions. Here, we demonstrate that the nanoscale charge transport and resistive switching behavior of VOx thin film can be tuned by modulating the substrate morphology. Particularly, the device prepared with flat-Si shows totally distinguished behavior in comprising of reactive ionetched-Si substrates. Interestingly, conductive atomic force microscopy current maps revealed the electric field inhomogeneity due to a change in substrate morphology. A reliable bipolar resistive switching behavior of the corresponding etched devices have been demonstrated. Due to an increase in the etching time of substrate, an increase in active area and decrease in work function was observed. Further, nanoscale synaptic functions were generated from the corresponding devices, showing a strong conduction path at preferential bright spots of the particular devices. Moreover, finite element simulations confirm the modulation in generation of localized current conduction in particular etched devices by applying tip voltages. These findings represent a new way to generate nanoscale artificial synaptic functions.
Keywords: Artificial synapse; Conductive atomic force microscopy; Finite elements simulation; Nano scale; Nanoscale artificial synapse; Resistive switching; Resistive switching behaviors; Substrate morphologies; Tunables; Two terminals; conductive atomic force microscopy; finite element simulation; Nanoscale artificial synapse; resistive switching; tunable